Flipping the researcher knowledge translation perspective on knowledge use: a scoping study. (September 2019) - Shibasaki, Sanchia; Sibthorpe, Beverly; Watkin Lui, Felecia; Harvey, Alistair; Grainger, Daniel; Hunter, Cass; Tsey, Komla
The first community of practice of Torres Strait Islander researchers in Australia was established to ensure knowledge translation efforts are effective in addressing the gap between "what is known" and "what is currently done" in policy and practice settings in the region. The scoping review involved a search of publicly accessible and relevant online databases and a rapid appraisal of systematic reviews and scoping studies of knowledge translation models and frameworks. The search identified 156 knowledge translation models and frameworks, of which 15 models and frameworks were selected for analysis. Selected models described knowledge use in terms of characteristics about the individual or the individual's context. Surprisingly, given the growth in information about knowledge translation and research impact, there appear to be very few knowledge translation models and frameworks that were framed from the perspective of the knowledge user, and there was no model or framework that was a stand-alone pull approach.